2022
DOI: 10.1155/2022/7411955
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of Snow and Ice Sports Health and Sports Information Collection System Based on Internet of Things

Abstract: The promotion of ice and snow sports not only provides professional athletes for the Winter Olympics but also acts as appreciative mass bases for ice and snow sports. The appearance of ice and snow sports will bring a new consumption pattern and develop a new ice and snow industry. In this paper, an Internet of Things (IoT)-based sports information collection system which is specifically designed and developed for the healthcare domain specifically in the snow and ice sports is proposed. The physiological para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…There are many experiences in the application design of ice and snow sports equipment, and a single statistical method cannot be accurately analyzed. In order to better carry out the corresponding research Cheng [ 20 ], this article combines the chaos theory model with the bee colony algorithm and comprehensively judges the experience design results through bionic algorithm. In the research process, corresponding constraints are added to the threshold and weight settings of the bee colony algorithm to ensure the accuracy of the calculation results [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many experiences in the application design of ice and snow sports equipment, and a single statistical method cannot be accurately analyzed. In order to better carry out the corresponding research Cheng [ 20 ], this article combines the chaos theory model with the bee colony algorithm and comprehensively judges the experience design results through bionic algorithm. In the research process, corresponding constraints are added to the threshold and weight settings of the bee colony algorithm to ensure the accuracy of the calculation results [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…ere are many experiences in the application design of ice and snow sports equipment, and a single statistical method cannot be accurately analyzed. In order to better carry out the corresponding research Cheng [20] Note. e red line is the improved bee colony algorithm proposed in this paper, and the blue line is the standard arti cial bee colony algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng [ 22 ] presented a sports data gathering system based on the Internet of Things (IoT). This study showed a sports data gathering system based on the IoT that was expressly developed and developed for the healthcare industry, specifically in sports.…”
Section: Related Workmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Implementation of Snow and Ice Sports Health and Sports Information Collection System Based on Internet of Things” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled "Implementation of Snow and Ice Sports Health and Sports Information Collection System Based on Internet of Tings" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%